Advantages And Strategy Of Services In Improving Loyalty Of Customers Bank - Dr Khamdan Rifa’i SE. (International Journal of Advanced Science and Technology, 2020)
The importance of services to customers will have an impact on strategic support to increase customer loyalty. The purpose of this study is to analyze the effectiveness of excellence and strategy in increasing customer loyalty. The method of study using qualitative methods by describing some symptoms or events relating to the problem or unit being studied. Data collection methods using interview techniques, leadership research samples and BRI BRI Syariah Banyuwangi bank customers. The results of the study concluded that competitive advantage needs to be supported by the right strategy, in this case, the existence of an effective Relationship Marketing system to increase loyalty and provide services, explanations and assistance related to banking products to customers. Secondly, the consistent application of Relationship Marketing principles as in point one above has significantly impacted Customer Loyalty on customers at BRI Syariah Syariah Banyuwangi. Third, Overall the services provided by BRI Syariah Banyuwangi Bank are in accordance with Relationship Marketing and line with the principles of Islamic economics, so that the competitive advantages that exist in Islamic banking can be optimally translated by BRI Syariah Banyuwangi Bank which makes this banking able to develop rapidly, especially in the past 3 years.